2019
DOI: 10.1016/j.mehy.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The cause-effect relationship between bone loss and Alzheimer’s disease using statistical modeling

Abstract: Background: Animal studies provide strong evidence that the CNS directly regulates bone remodeling through the actions of the hypothalamus via two distinct pathways, the neural (mediated by leptin) arm and neurohumoral (mediated by neurohormones and growth factors) arm. The impact of AD on central regulatory mechanisms of bone mass is not known. Objectives: To test a model that assesses the relationship between hypothalamic atrophy and bone loss in Alzheimer’s disease (AD) and potential mediation through neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition, predisposing conditions for sarcopenia, such as insulin resistance, inflammation, and oxidative stress, are also associated with cognitive dysfunction 32 . Although some of these mechanisms remain uncertain, studies have shown the link between bone loss, sarcopenia, and cognitive impairment [33][34][35] . Therefore, regular physical activity with strength exercise is recommended to prevent cognitive impairment in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, predisposing conditions for sarcopenia, such as insulin resistance, inflammation, and oxidative stress, are also associated with cognitive dysfunction 32 . Although some of these mechanisms remain uncertain, studies have shown the link between bone loss, sarcopenia, and cognitive impairment [33][34][35] . Therefore, regular physical activity with strength exercise is recommended to prevent cognitive impairment in the elderly population.…”
Section: Discussionmentioning
confidence: 99%
“…(6) Further, retrospective studies have demonstrated that both low BMD and osteoporosis diagnosis were significant predictors of progression from mild cognitive impairment to diagnosed dementia, suggesting that bone loss may precede some of the clinical manifestations of AD. (7,8) Skeletal muscle has also been shown to be negatively impacted by AD, based on evidence that female and male patients progressively lose skeletal muscle mass and strength as disease progression worsens compared to age and sex-matched controls, suggesting that AD may be exacerbating age-related loss of strength. (9,10) However, whether bone and muscle loss are a direct result of the neurodegeneration or occurs due to a shared mechanism active in both brain and musculoskeletal tissues remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Aβ induces the differentiation and activation of osteoclasts, resulting in the promotion of bone destruction (Cui et al, 2011 ; Li et al, 2016 ). Indeed, neuronal dysfunction with the brain structure changes in AD has been suggested to reduce the bone mass (Loskutova et al, 2010 , 2019 ). This is supported by the high incidence of fracture in AD patients with a low bone mineral density (Friedman et al, 2010 ; Wang et al, 2014 ).…”
Section: Neuroinflammation In Admentioning
confidence: 99%